DIFFERENCES IN KNOWLEDGE, PREPAREDNESS, PERCEIVED RISK, AND PREVENTIVE BEHAVIOR IN IMPLEMENTING HEALTH PROTOCOLS BETWEEN POST INFECTED AND NEVER INFECTED WITH COVID-19 IN POLDA ACEH - Maulita; Agussabti (RADJA PUBLIKA, 2023)
This study aims to determine differences in knowledge, preparedness, perceived risk, and preventive behavior in implementing health protocols between post-infected individuals and those who have never been infected with Covid-19 at the Aceh Regional Police. This study was obtained by means of purposive sampling involving 330 respondents, divided into 165 respondents who had been infected with COVID-19 and 165 who had never been infected with COVID-19 with a validity value above 0.3 and a Cronbach alpha value above 0.6. The data collection technique used a questionnaire/questionnaire and the data analysis technique used the chi-square test. The results showed that knowledge, preparedness, perceived risk, and preventive behavior of respondents who had been infected with Covid-19 were better and had a different significance value below 0.05.